Effects of intravenous bolus injection of nicorandil on renal artery flow velocity assessed by color Doppler ultrasound. Issue 1 (January 2017) - Shimamoto, Yukiko; Kubo, Takashi; Tanabe, Kazumi; Emori, Hiroki; Katayama, Yosuke; Nishiguchi, Tsuyoshi; Taruya, Akira; Kameyama, Takeyoshi; Orii, Makoto; Yamano, Takashi; Kuroi, Akio; Yamaguchi, Tomoyuki; et al.
Abstract: Background: Previous animal studies have shown that a potassium channel opener, nicorandil, provokes vasodilation in renal microvasculature and increases renal blood flow. We conducted a clinical study that aimed to evaluate the effect of nicorandil on renal artery blood flow in comparison with nitroglycerin by using color Doppler ultrasound. Methods: The present study enrolled 40 patients with stable coronary artery disease who had no renal arterial stenosis and renal parenchymal disease. The patients received intravenous administration of nicorandil ( n = 20) or nitroglycerin ( n = 20). Before and after the administration, renal artery blood flow velocity was measured by color-guided pulsed-wave Doppler. Results: The peak-systolic, end-diastolic, and mean renal artery blood flow velocities before the administration were not different between the nicorandil group and the nitroglycerin group. The peak-systolic (79 ± 15 cm/s to 99 ± 21 cm/s, p < 0.001; and 78 ± 19 cm/s to 85 ± 19 cm/s, p = 0.004), end-diastolic (22 ± 5 cm/s to 28 ± 8 cm/s, p < 0.001; and 24 ± 6 cm/s to 26 ± 6 cm/s, p = 0.005) and mean (41 ± 6 cm/s to 49 ± 9 cm/s, p < 0.001; and 43 ± 9 cm/s to 45 ± 9 cm/s, p = 0.009) renal artery flow velocities increased significantly in either group. The nominal changes in the peak-systolic (20 ± 10 cm/s vs. 7 ± 8 cm/s, p < 0.001), end-diastolic (5 ± 4 cm/s vs. 2 ± 3 cm/s, p = 0.001), and mean (8 ± 5 cm/s vs. 2 ± 2 cm/s, p < 0.001) renal artery blood flow velocities were significantly greater in the nicorandil group compared with the nitroglycerin group. Conclusion: Intravenous nicorandil increased renal artery blood flow velocity in comparison with nitroglycerin. Nicorandil has a significant effect on renal hemodynamics.